2021
DOI: 10.3390/mca26010013
|View full text |Cite
|
Sign up to set email alerts
|

Differential Evolution under Fixed Point Arithmetic and FP16 Numbers

Abstract: In this work, the differential evolution algorithm behavior under a fixed point arithmetic is analyzed also using half-precision floating point (FP) numbers of 16 bits, and these last numbers are known as FP16. In this paper, it is considered that it is important to analyze differential evolution (DE) in these circumstances with the goal of reducing its consumption power, storage size of the variables, and improve its speed behavior. All these aspects become important if one needs to design a dedicated hardwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In [10], de la Fraga analyzes the use of numbers with 16 bits in a conventional Differential Evolution (DE) algorithm. It is shown that the additional use of fixed point arithmetic can speed up the evaluation time of the objective function.…”
mentioning
confidence: 99%
“…In [10], de la Fraga analyzes the use of numbers with 16 bits in a conventional Differential Evolution (DE) algorithm. It is shown that the additional use of fixed point arithmetic can speed up the evaluation time of the objective function.…”
mentioning
confidence: 99%